Field notes contributed by Woodward H. Brown, winter 1978-1979 - Brown, Woodward H.et al (1978)
Winter report of birds found in and around the Des Moines area contributed by Woodward H. Brown. The sighting of a Red-shouldered Hawk is underlined in red. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report winter of 1978-1979. Epson - sheet feed/flatbed